INDUSTRIAL GROWTH, HUMAN DEVELOPMENT INDEX, GENDER DEVELOPMENT INDEX AND POPULATION ON THE SEVERITY OF POVERTY IN CENTRAL JAVA - Kusumawati, Bella; Suryanto, Suryanto; Sarjiyanto, Sarjiyanto (Universitas Tidar, 2024)
Poverty is a problem that affects most countries in the world, including Indonesia. Central Java Province is a region on the island of Java that occupies the second position with the highest poverty rate compared to other provinces on the island of Java. The problem of poverty must be addressed immediately so that an analysis of the factors that influence poverty is needed so that it is hoped that poverty alleviation programs can be right on target. This research aims to examine the influence of industrial growth, HDI, population and GDI on poverty levels in Central Java Province in 2011-2020. The data used is panel data which is analyzed using Random Effect Model panel data regression with a total of 35 regencies/cities in Central Java as research objects. The processing results show that there is a negative and significant influence between Industrial Growth, HDI and GDI on Poverty Levels. Meanwhile, population size does not have a significant influence on poverty levels. This means that with industrial growth, HDI and GDI development can reduce the severity of poverty. The Central Java Provincial Government must create a good environment for the growth and development of industrialization, as well as increasing gender-oriented human development.